(untitled) (Research, Society and Development, 2023)
Ectopic pregnancy is a pathology that presents a wide range of clinical manifestations, with numerous risk factors and a significant rate of complications. The pathophysiology refers to the implantation of the blastocyst. The most commonly reported clinical picture is related to vaginal bleeding with or without abdominal symptoms, but the characteristics can be variable because it is an embryonic implantation in the wrong place. There is a frequent association with pregnancies conceived through in vitro fertilization. Rarely, an ectopic pregnancy implants in the cornual region. Diagnosis is based on visualization of an extrauterine gestational sac with yolk sac or embryo, positive serum chorionic gonadotropin, and no products of conception on uterine aspiration or visualization on surgery. Treatment is related to the severity and symptoms presented by the individual. The objective of this study is to report a case of ruptured cornual ectopic pregnancy with advanced gestational age, showing the management and the form of treatment chosen for the patient.